Bending behavior of thermoplastic composite sheets : viscoelasticity and temperature dependency in the draping process - Ropers, Steffen (Springer, 2017)
Within the scope of this work, Steffen Ropers evaluates the viscoelastic and temperature-dependent nature of the bending behavior of thermoplastic composite sheets in order to further enhance the predictability of the draping simulation. This simulation is a useful tool for the development of robust large scale processes for continuously fiber-reinforced polymers (CFRP). The bending behavior thereby largely influences the size and position of wrinkles, which are one of the most common processing defects for continuously fiber-reinforced parts. Thus, a better understanding of the bending behavior of thermoplastic composite sheets as well as an appropriate testing method along with corresponding material models contribute to a wide-spread application of CFRPs in large scale production. Contents Thermoplastic Prepregs Draping Simulation of Thermoplastic Prepregs Bending Characterization of Textile Composites Modeling of Bending Behavior Target Groups Researchers and students in the field of polymer, lightweight, computational, or mechanical engineering Practitioners in the automotive industry, polymer processing, lightweight design, computational aided engineering (CAE) About the Author Steffen Ropers studied mechanical engineering at the University of Erlangen-Nuremberg, Germany, and the University of Wisconsin-Madison, U.S., with majors in polymer engineering and manufacturing technology. He is currently employed at the materials and processes department of a notable automotive OEM. <.
Keywords: Thermoplastic composites -- Mechanical properties.; Finite element method.; elektronické knihy; electronic books